Congenital Aortic Vascular Ring: In-Utero Sonographic Assessment of Tracheal Patency and Postnatal Outcome - Achiron, Reuven Ryszard; Kassif, Eran; Gilboa, Yinon; Salem, Yishay; Jakobson, Yizhak; Raviv-Zilka, Lisa; Kivilevitch, Zvi (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Objective Congenital aortic vascular ring may present after birth with variable degrees of respiratory distress due to tracheal compression. The aim of this study was to prospectively evaluate in utero tracheal patency in correlation with postnatal outcome.Methods During an eight-year period, fetuses with aortic arch abnormality encircling the trachea and forming a complete ring were recruited for the study. Tracheal patency was classified as: no compression, partial compression, or complete compression. Postnatal MRI/CTangio studies were performed and outcome data was retrospectively analyzed from the medical records.Results Among the 46 fetuses recruited to the study, 38 had right aortic arch (RAA), and 8 presented with double aortic arch (DAA). In the RAA group 35 (92.1 %) of the fetuses presented no compression and 34 (97.1 %) of them were asymptomatic in the long-term follow-up. Three fetuses (7.9 %) in this group presented in utero compression: one was terminated at 16 weeks of gestation due to associated ominous findings, and the other two had mild respiratory symptoms around 12 months of age and underwent surgery with a good outcome. In the DAA group, all fetuses presented in utero with tracheal compression. Seven showed partial and one complete compression. Among the seven with partial compression, six were symptomatic and underwent surgery. The case with severe airway occlusion had emergency tube insertion in the delivery room and underwent surgery at 7 days but died from severe respiratory complications.Conclusion This is the first study to evaluate in utero tracheal patency in cases with vascular ring. It allows better prenatal and postnatal workup and follow-up including potentially life-threatening respiratory failure.
Keywords: fetus; ultrasound; aortic vascular ring; obstetrics